Palm distribution patterns in the southwestern Brazilian Amazon: Impact of a large hydroelectric dam - Santos, Ednéia A. dos; Medeiros, Marcelo Brilhante; Ferreira, Evandro José Linhares; Simon, Marcelo Fragomeni; Oliveira, Washington Luís; Costa, Flávia Regina Capellotto (Forest Ecology and Management, 2020)
Mega hydroelectric dams cause loss of habitat for many species and lead to local or regional extinction. Despite these dire facts, little is known about the impact of these mega-dams on Amazonia. Using palms as a model, we investigated this question by sampling 26 1-ha plots distributed in the influence areas of the Jirau mega-dam in southwestern Brazilian Amazonia. We examined palm community patterns and species distributions as a function of environmental variables, as well as the effect of this large dam on plant survival. Palm communities on the banks of the Madeira River differ among three main habitats sampled (campinarana, terra-firme and várzea forests), and these differences are associated with the gradient of C, pH, N, P, soil texture, slope, and depth to the water-table. The level of the Madeira River raised after the construction of the Jirau mega-dam, directly affecting the populations of 61.3% of the palm species, particularly those species associated to areas with silty soils, low slope, and low depth to the water-table. Várzea and terra-firme forests near the river, as well as low-lying plots, even those distant from the river, were affected by the filling of the reservoir. Várzea forests and campinaranas had a greater proportion of palm species flooded by the reservoir and the reduction of water-table depth. Várzea forests and campinaranas harbor distinct palm communities from the terra-firme forests and require priority in conservation policies and management to mitigate harmful environmental impacts in the Amazon. © 2020 Elsevier B.V.
Keywords: Dams; Ecosystems; Extreme Weather; Forestry; Groundwater; Hydroelectric Power Plants; Reservoirs (water); Rivers; Textures; Arecaceae; Campinarana; Conservation Policy; Environmental Variables; Extreme Weather Events; Species Distributions; Terra-firme Forests; Water Table Depths; Environmental Impact; Conservation Planning; Conservation Status; Dam; Deciduous Tree; Environmental Impact; Environmental Management; Environmental Planning; Extreme Event; Forest Ecosystem; Hydroelectric Power; Plant Community; Reservoir; Dams; Depth; Ecosystems; Forestry; Forests; Patterns; Rivers; Water; Amazonia; Brasil; Madeira River; Arecaceae